Mayotte’s seismo-volcanic “crisis” in news accounts (2018–2021) - Devès, Maud H.; Moirand, Sophie; Le Vagueresse, Louise; Robert, Geoffrey (Comptes Rendus. Géoscience)
Mayotte’s seismo-volcanic crisis gave rise to extensive media coverage in the local, regional and national daily press. Analyzing the news narratives allows us to bring to light the representations that readers are confronted with when they try to inform themselves about the situation. This article brings together the sciences of risk, language and communication in order to analyse these pluri-vocal narratives, in which the scientific community is given pride of place. It shows how the voices of the main actors (the inhabitants, the administrative and scientific authorities) are put on the stage, conveying differing representations, differing forms of explanation and contributing to an effect of “enunciatory muddling”. It aims to provide food for thought for people called upon to intervene in the media, in Mayotte or elsewhere.